A Novel Approach for Prediction of Sensitivity toward the Electrical Discharge of Quaternary Ammonium‐based Energetic Ionic Liquids or Salts. Issue 19 (23rd July 2018) - Nazari, Behzad; Keshavarz, Mohammad Hossein; Jafari, Mohammad; Jafari, Fatemeh
Abstract : Sensitivity toward electrical discharge (electric spark or electrostatic sensitivity) is an important safety parameter for assessment of working with new energetic compounds including ionic molecular energetic materials. This work introduces a novel simple correlation to assess the electrostatic sensitivity of quaternary ammonium‐based energetic ionic liquids or salts, which are based on elemental composition and the structure parameters of specific cations and anions. For 66 ionic molecular systems as a training set, the Root Mean Square Error (RMSE), Mean Absolute Error (MAE), and Maximum of Errors (Max Error) of predictions for the new model are 0.17, 0.15, and 0.31 J, respectively. The reliability of models was also tested for further 21 ionic compounds, which give the values of RMSE, MAE, and Max Error of 0.13, 0.11, and 0.25 J, respectively. Thus, the accuracy of the novel method for prediction of the electrostatic sensitivity of quaternary ammonium‐based energetic ionic liquids or salts is relatively good with respect to high uncertainties in experimental data. Abstract :